Diagnostic comparison between cytological and molecular analysis for the detection of Mycoplasma haemofelis in resident cats of the city of Pereira, Risaralda, Colombia - Caballero Méndez, Lyda (2022)
Mycoplasma haemofelis is the most pathogenic haemotropic species that affects felines by parasitizing red blood cells and inducing a haemolytic process that can lead to anaemia. The present study aimed to determine the prevalence of this infection in domestic felines from the city of Pereira, Risaralda, Colombia. Samples from 104 domestic felines between 1 and 10 years of age were analysed. Blood samples were taken for cytological (haematological parameters) and molecular analysis by PCR. Additionally, the possible risk factors associated with the presence of M. haemofelis (age, sex, vaccination status and geographical area of origin) were evaluated. The prevalence by molecular analysis was 80.8%, while it was 80.7% with the Giemsa stain and 81.7% with the Wright stain, and the youngest animals (1-2 years) being the most affected. A significant statistical correlation (p=0.0038) of age with the infection was evidenced as an associated risk factor in this area of the country.